Characterizing neurocognitive impairment in young people with major depression: state, trait, or scar?. Issue 10 (21st July 2016) - Allott, Kelly; Fisher, Caroline A.; Amminger, Gunther Paul; Goodall, Joanne; Hetrick, Sarah
Abstract: Background: Major depressive disorder (MDD) affects a quarter of adolescents and young adults and is associated with the greatest global burden of disease in this population. There is a growing literature, mostly in adults, showing that significant neurocognitive impairments are common in MDD. It remains unclear whether these impairments are pre‐existing trait markers of MDD, state‐related impairments that fluctuate with depressive symptoms, or 'scar' impairments that worsen with illness progression. The aim of this study is to provide a conceptual framework for understanding MDD and neurocognitive impairment in adolescence and young adulthood (ages 12–25 years). Method: Examination of the evidence for neurocognitive deficits as trait, state, and scar features of MDD according to different study designs (family studies, premorbid studies, current depression, remitted depression, and longitudinal studies with repeated assessment) was conducted. Results: The few premorbid and family studies conducted in youth provide equivocal evidence for neurocognitive impairments as trait markers of MDD. The presence of state‐based neurocognitive impairment remains unclear as evidence comes mostly from cross‐sectional studies. There are a limited, but growing number of longitudinal studies with repeated neurocognitive assessment in youth. Studies that examined neurocognition prior to the onset of MDD and with long‐term follow‐up provide tentative evidence for neurocognitive scarring. Conclusion: Neurocognitive impairment is a feature of MDD in adolescents and young adults. To better understand the nature, timing, and pattern of impairment, longitudinal studies that examine neurocognition before and after the development of full‐threshold MDD, including following recurrence are needed. This knowledge will have important implications for mechanisms, prevention, and treatment of MDD in youth. Abstract : A conceptual discussion and examination of the evidence for neurocognitive deficits as trait, state, and/or scar features of major depressive disorder in adolescence and young adulthood. There is preliminary evidence for scar‐related neurocognitive impairments in youth depression. However, the evidence for trait and state impairments is inconclusive, primarily due to a lack of rigorous longitudinal studies.